CaM/CaMKII mediates activation and proliferation of hepatic stellate cells regulated by ASIC1a - Liu, Hui; Lu, Wei-Li; Hong, Hai-Qin; Li, Meng-Jun; Ye, Man-Ping; Rao, Qiu-Fan; Kong, Jin-Ling; Luan, Shao-Hua; Huang, Yan; Hu, Qing-Hua; Wu, Fan-Rong (Frontiers in Pharmacology, 2022)
The activation of hepatic stellate cells (HSCs) is closely related to hepatic fibrosis and plays a key role in its occurrence and development. In the damaged liver, inhibition of the activation, proliferation, and clearance of HSCs is an important therapeutic strategy. However, the mechanism underlying the activation of HSCs is not completely clear. Acid-sensitive ion channel 1a (ASIC1a) is a cation channel activated by extracellular acid, which is responsible for the transport of Ca2+ and Na+ and participates in the activation of HSCs and the occurrence and development of many inflammatory diseases, suggesting that ASIC1a plays an important role in liver fibrosis. A previous study by the project team found that when the membrane channel protein ASIC1a was opened, intracellular Ca2+ levels increased, the expression of CaM/CaMKII in HSCs was high, and HSC was activated and proliferated. Therefore, we established an SD rat model of hepatic fibrosis and induced HSC-T6 activation by stimulating ASIC1a with acid in vitro. In vivo, CCl4 was used to induce liver fibrosis in rats, and different doses of KN93 (0.5, 1, and 2 mg/kg/d) and colchicine (0.1 mg/kg/d) were administered. Eight weeks later, the activities of ALT and AST in serum were measured and hematoxylin-eosin and Masson staining in liver tissue, and immunohistochemistry analysis were performed in SD rats. The expressions of ASIC1a, α-SMA, Collagen-1, CaM, and CaMKII were detected. In vitro, we activated HSC-T6 cells by stimulating ASIC1a with acid. The results showed that inhibition of ASIC1a could improve acid-induced HSCs activation. In addition, CaM/CaMKII was expressed in HSC of rats with hepatic fibrosis regulated by ASIC1a. After blocking or silencing the expression of CaMKII, the fibrosis marker protein can be down-regulated. KN93 also reduced inflammation and improved the activation, proliferation and fibrosis of HSC. In summary, we concluded that CaM/CaMKII participates in ASIC1a regulation of the proliferation and activation of HSC and promotes the occurrence of liver fibrosis.